The Intersection of Variability in Gross Motor Performance and Adaptive Behavior in Young Autistic Children: Combining Video Data Analysis and Standardized Assessments - Ayoub, Maria J; Keegan, Laura; Luo, Michele Z; Tager-Flusberg, Helen; Chenausky, Karen; Maffei, Marc F; Green, Jordan R; Gill, Simone V (Autism research, 2025)
Autism research has shown relationships between motor skills and other developmental domains. However, little research has examined variability in gross motor performance and its potential relation to adaptive behavior in this population. The purpose of this study was to use task-based measures of gross motor performance to quantify variability and to determine if gross motor variability was associated with adaptive behavior. We collected video data of autistic children aged 4-7 years (N = 71) performing two task-based measures of gross motor performance: walking over flat ground and balancing on one leg. We also computed walking behaviors: behaviors exhibited by children during walking (e.g., jumping). We used the Vineland Adaptive Behavior Scale Adaptive Behavior Composite (VABS-ABC) to measure adaptive behavior. Results showed high intra-subject variability during walking skill, walking behaviors, and balance performance. Less variable walking velocity was correlated with higher adaptive behavior scores. In contrast, less variability in walking behaviors was correlated with lower adaptive behavior scores. These results highlight that variability in gross motor performance may be a feature of ASD and examining gross motor variability in relation to other developmental domains (e.g., adaptive behavior) may provide a more comprehensive understanding of autism.